Comparison of Analytical and Numerical Approach in Bridge Crane Solution - Molnár, Denis; Blatnický, Miroslav; Dižo, Ján (Manufacturing Technology Journal, 2022)
A crane bridge is a dominant component of all bridge crane. It is imperative to pay attention on its strength features and go through a strength analysis. The introductory part of this paper points out characteristics of a bridge crane, mainly a crane bridge and materials used to produce the crane bridge, namely S235 structural steel. The paper set out the strength analysis of the main girder of a single girder bridge crane model in the means of comparing analytical and numerical solutions. The calculations take into account the load of the main beam in its centre according to the standard STN 27 0103. The bridge crane model is designed for a 500 kg load carrying capacity. The numerical solu-tions are represented by finite element method (FEM) analysis in Ansys software. The intention is to determine the deformation of the main girder depending on the weight of a load and a hoist, to de-termine the maximum deflection and resulted bending stress. Furthermore, one of the purposes is to create the precise 3D CAD model of the main girder. The 3D CAD software Catia V5 was used to design the bridge crane model. The strength analysis of the main girder of IPE 100 profile was performed by the FEM analysis using the Ansys software and by analytical calculations. The results ob-tained by the computing software Ansys were only slightly smaller in comparison with the analytical calculations. Results obtained by Ansys can be considered as more accurate. It can be concluded, such the designed and strength-checked main girder can be in the future put into a production.
Keywords: Bridge crane; Girder; Strength analysis; Analytical calculation; FEM analysis